The Kitty Hawk Venture : a novel about continuous testing in DevOps to support continuous delivery and business success /: a novel about continuous testing in DevOps to support continuous delivery and business success. ([2018]) - Scheaffer, Jeffrey; Ravichann, Aruna; Martins, Alex
No abstract available